Steady state kinetic analysis of Legionella pneumophila Cu+ transport ATPase: The activation by Cu+ and ATP ) - Placenti, Maria Agueda (2021)
P-type ATPases are a family of membrane proteins which couple ATPhydrolysis to the transport of substrates across biological membranes. Withinthem, Cu + -ATPases are the most widespread and conserved heavy metal iontransporting ATPases (PIB-ATPases). Its reaction cycle is assumed to bedescribed by the so-called Albers-Post model postulated for the most studied P-ATPases such as the Na + ,K + -ATPase or the Ca 2+ -ATPases. However, as somestructural and functional particularities arise for Cu + -ATPases, several authorsposit some doubts about their reaction cycle mechanism. The aim of our work isto perform a functional characterization of Legionella pneumophila Cu⁺-ATPase(LpCopA) by measuring steady state ATPase activity. Cu + -ATPase activity of theenzyme presents a maximum at ∼37ºC and pH 6.6-6.8. Phospholipids enhanceLpCopA Cu + -ATPase activity in a non-essential mode where optimal activity isachieved at an asolectin mole fraction of 0.15 and an amphiphile-protein ratio of~30000. As described for other P-ATPases, Mg 2+ acts as an essential activator.When evaluating the role of ATP and Cu + in the reaction cycle of LpCopA weobserved that ATPase activity increases as Cu + concentration increases with afunctional dependence that can be described by a sum of two hyperboles. Onthe other hand, the increment on ATP concentration in the reaction mediaproduces an increment of ATPase activity that can be described by a hyperbolaplus a constant value. Based on that, and the [Cu + ] and [ATP] dependencies ofthe best fitting parameters of the functions pointed above, we propose aminimal reaction scheme for LpCopA catalytic mechanism that contemplatestwo enzyme conformations with different affinities for ATP, enzymephosphorylation and binding of at least two Cu + ions with different affinities. Thismodel is compatible with the structural information available and the maincharacteristics of the reaction cycle models for the most characterized P-TypeATPases.